Peningkatan Kemampuan Menulis Teks Prosedur Siswa Melalui Metode Clis - Nuri Nuri (LPPM Press, 2010)
Abstract: this research introduced a new teaching strategy that is ChildrenLearning in Science (CLIS) in learning English as foreign language, especially inthe students’ writing. CLIS provides logical subject of theory, facts, problemsolving, and application by doing an experiment. By learning through science,students can explore their scientific skill in finding the answer of a realisticproblem happened. This research is in the form of Classroom Action Research(CAR) that had been conducted into two cycles. The analysis copes with theteacher and students’ activities in the process of teaching learning and thestudents’ respond. The research method used is descriptive with research designof qualitative. The population of the research is the tenth grade students of MAN 2Madiun which has 192 students in all. The result of research shows an increasingresult on the teacher and students’ activities as well as students’ affective andcognitive score that supported with students’ responses toward CLIS.